Lernaea (Anchorworm) Infestations in Fish - Natalie Steckler; Roy P. Yanong (EDIS)
Lernaea species, commonly known as “anchorworms,” are crustacean, copepod parasites that can infect and cause disease and mortality in many types of freshwater fishes, especially wild-caught and pond-raised species. Infestations with Lernaea are most prevalent in the summer months and occur more commonly in stagnant or slow-moving water bodies. This 4-page fact sheet was written by Natalie Steckler and Roy P. E. Yanong and published by the UF Department of Fisheries and Aquatic Sciences, December 2012.